(untitled) (Biological Sciences - PJSIR, 1995)
Samplesof fruitsandyegetablesprocuredfromthegrowers’ fieldsandmainsellingpointsofNorth WestFrontier Province, Islamabad andQuetta/Pishindistrictsof BalochistanduringDec.1990 andSep. 1992, weremonitoredforor- ganochlorine, organophosphorus and pyrethroidpesticides.Among the300 samplesscreened, 121 samples contained a variety of pesticides.Thirty-eight samplescontained pesticideresiduesabove maximum residue limits (MRLs)pro- posed by FAO/WHO, while for several samples, no MRL was available for detected pesticides but high amounts of residues were found tobe present in certain commodities.The remainingsamplesdid not contain detectable pesticide residues.